Ambidextrous human resource practices and individual creativity—A cross-layer multi-time analysis based on psychological capital and QLMX - Zhao, Fuqiang; Wang, Longdong; Chen, Yun; Hu, Wei (Frontiers in Psychology, 2022)
As an important factor in enhancing individual creativity, employees’ psychological capital has been widely tested by scholars. However, the effects of ambidextrous human resource practices (AHRP) on individual creativity has not been confirmed. On the basis of the theories of social exchange and resource preservation, we explored the mechanism of AHRP's impact on individual creativity using three-point data collected from March to September 2021 from 23 large enterprises in the service, finance, construction, and education sectors in five Chinese cities: Wuhan, Shanghai, Guangdong, Shenzhen, and Zhengzhou. A cross-layer regression and a Monte Carlo sampling analysis were performed on 135 pairs of leaders and 810 employees. In addition, we tested the cross-layer mediating effect of the psychological capital between AHRP and individual creativity and the boundary effect of the quality of leader–member exchange (QLMX) in the cross-layer effect. Research results indicate that (1) AHRP have positive effects on individual creativity across layers; (2) psychological capital mediates the cross-layer relationship between AHRP and individual creativity; (3) QLMX moderates the direct effect of AHRP on employees’ psychological capital; and (4) QLMX moderates the indirect effect of AHRP on individual creativity through psychological capital. The research conclusions lay a theoretical foundation for AHRP at the organizational level and provide a guiding reference for the enhancement of employee creativity at the individual level.